Strategi Pelaku Umkm Dan Peran Pemerintah Di Era Persaingan Global Dalam Meningkatkan Perekonomian Di Kabupaten Tegal - Amrina, Dania Hellin; Yusabiran, Rifqi (Ekopem: Jurnal Ekonomi Pembangunan, 2024)
Micro, Small, and Medium Enterprises (MSMEs) make a large economic contribution to the country and act as an important catalyst for the growth of people's income. Micro, Small, and Medium Enterprises (MSMEs) have a significant impact in driving innovation, reducing unemployment, and increasing compensation due to their tendency to integrate their employees. This article aims to analyze strategies that can be implemented by micro, small, and medium enterprises (MSMEs) to overcome operational challenges and secure their business continuity in the long term amidst a business environment characterized by global competition. In addition, it is important for the government to actively encourage the sustainability of Micro, Small and Medium Enterprises. This goal can be achieved through various methods, such as establishing appropriate fiscal policies, facilitating the development of strong infrastructure, and offering training opportunities. This research uses quantitative research methodology, utilizing descriptive techniques to explain and communicate the results. By complementing primary data obtained through administering questionnaires with secondary data obtained from previous investigations, this research increases the completeness of its analysis. To achieve this goal, MSME players need to consider many elements such as advances in technology and transportation, competition in the free market, and effective marketing techniques. If these variables are used effectively and receive sufficient government support, Micro, Small, and Medium Enterprises (MSMEs) do not need to worry about the long-term sustainability of their businesses. Apart from that, the country's economy as a whole will also experience positive growth and development.